Impact Des Conflits Armes Sur La Sante Maternelle En Cote d’Ivoire: Cas Des Conflits Armes De 2002 Et De 2010 - Hélèna Epse Tra, Djessou Flore Marie (European Scientific Journal, ESJ, 2018)
The "new conflict" that emerged in the 90s, mainly in developing countries, is a major obstacle to improving health. Quantitative studies of the impact of armed conflict on maternal health indicators are still fragmentary and scarce. The purpose of this study is to analyze the impact of the 2002 and the 2010 conflicts on maternal health in Côte d'Ivoire. In this study, we choose a particular type of health care service with assisted delivery in a health center. We use the parametric difference using the difference method to estimate our parameter of interest. Also, we use the propensity score technique and the standard error bootstrap technique to regulate some double difference hypotheses. In making our estimates, we use survey data including the MICS 2000 and 2006 and EDSCI 2012. Our results show that, globally, the crisis of 2002 had a negative effect on the use of assisted delivery in the CNO zone (Center North and West) (-0,708). The same is true for the post-election crisis (-0,514). On the other hand, in South and Abidjan zone, the 2002 crisis had no significant effect, while that of the 2010 crisis had a positive effect (+0,628). The conflicts of 2002 and 2010 therefore constituted a major impediment to access to maternal health care services for households living in CNO zone.